Morphology and semantics - the basis of Croatian case - Jelaska, Zrinka (Array, 2002)
The authors analyzed nouns in the language of Croatian children from both morphological and semantic perspectives. The analysis of morphologically different cases is contrasted with the analysis of different semantic roles that the cases carry. Being a very rich language morphologically, Croatian turns out to be far simpler in the early stages of a child's language development. A child reflects the characteristics of the input language, not overall, but with the words shared with the input. In addition to the simplicity found in child language, the authors also found that tokens are usually concentrated around prototypical members (morphological, semantic) in both the child and the input languages.